GENRE ET PRODUCTION AGRICOLE DANS LES COOPERATIVES DU NORD DE LA CÔTE D’IVOIRE - Ferdinand, Vanga Adja (European Scientific Journal, ESJ, 2012)
Rural women are generally marginalized in access to land and in agricultural income generating activities. This study help assessing women contribution in agricultural production through farmers’ organizations in savannah region in Côte d’Ivoire. As regarding data collection, group (focus group) and individual interviews were used. Qualitative data will be analyzed using dialectic and comparative methods. Obtained results show a situation in which women are overwhelmingly important in northern farmers union (COFONI) with 63%. By integrating women in its activities, the farmers’ organization COFONI benefited from projects financed by organizations of development.